Research Trends and Hotspots of Extracorporeal Membrane Oxygenation: A 10-Year Bibliometric Study and Visualization Analysis - Wang, Huaqin; Deng, Siqi; Fan, Xiaoyu; Li, Jinxiu; Tang, Li; Li, Yamin; Yu, Bo (Frontiers in Medicine, 2021)
Objective: To determine the research hotspots and trends in the field of extracorporeal membrane oxygenation (ECMO), and to provide a reference for further and wider research in the future. Methods: The literatures on ECMO from January 2011 to July 2021 in the Web of Science Core Collection (WOSCC) database were searched, and Citespace5.8.R1 software was used to conduct bibliographic and visual analysis on the literature by country, institution, author and keywords. Results: A total of 5,986 articles were enrolled. According to an observation, the number of articles published in the past decade has increased, especially from 2019 to 2020. The USA had the largest number of publications, while less ECMO related studies were conducted among non-developed countries. The University of Michigan (Univ Michigan) was the institution that had the largest number of publications and the highest centrality, and Daniel B was the author who had the largest number of publications. However, more inter-institutional cooperation among author teams was needed. The focus of existing ECMO research has primarily been on the treatment of patients suffering from severe cardiopulmonary failure, and the prevention and management of complications during the application ECMO. Conclusion: Inter-regional and inter-institutional cooperation and exchanges should be carried out among ECMO research teams and institutions. The suggested research direction is to further broaden the application scope of ECMO, while determining the ways to reduce the incidence of complications and the cost, cultivate specialized team talents, and promote the application thereof.